Maintaining cost-effective access to antiretroviral drug therapy through a collaborative approach to drug procurement, consensus treatment guidelines and regular audit: the experience of London HIV commissioners and providers. Issue 2 (16th February 2012) - Foreman, Claire; Gazzard, Brian; Johnson, Margaret; Sharott, Peter; Collins, Simon
Abstract : Background: In the UK, meeting the £20 billion efficiency challenge in the NHS requires new approaches to protect quality and improve productivity. In London, clinicians, people living with HIV and commissioners are collaborating to reduce the cost of antiretrovirals as part of the Quality Innovation Productivity and Prevention agenda. Objectives: To describe how collaboration in antiretroviral procurement in 2011/2012 aimed to significantly reduce drug acquisition costs, ensure equity of prescribing and protect the quality and experience of care and treatment for patients. Methods: Greater clinical leadership and engagement and involvement of patient representatives enabled an approach to drug procurement focused on clinical outcomes at a patient and population level while reducing cost. Consensus guidelines for implementation were developed and agreed by all London lead clinicians while people living with HIV produced a patient information leaflet to explain the tender process and outcomes. A planned audit is underway at all services to monitor prescribing changes and outcomes for those on treatment. Results: HIV clinicians, pharmacists and patient representatives were directly involved in this novel therapeutic tendering approach to antiretroviral drug procurement. Modelling indicates that £8–£10 million savings will be released through the process over 2 years. Conclusions: Clinically led therapeutic tendering of antiretroviral drugs provides an opportunity to protect quality and improve productivity in HIV. The approach is novel in HIV in the UK, and the emergent learning has implications for quality and cost improvement in HIV spending in the UK and potentially in other countries.